Computer Aided Geometric Design (CAGD) : comparison study between cubic B-spline, Cubic Trigonometric Spline and Cubic Trigonometric Bezier on Chinese Calligraphic / Nur Nabilah Che Draman - Che Draman, Nur Nabilah (2018)
Chinese calligraphic is the type of writing that can be expressed the feeling by handwriting and its very prized among China’s cultured. Calligraphic are very particular about its shape, smooth line and continuity to produce the perfect curve. The method that have been used in this research are Cubic Trigonometric Bezier, Cubic Trigonometric Spline and Cubic Spline which is determined the best curve in generating the Chinese Calligraphic. However, in this research the method that give a smoothness curve is Cubic Trigonometric Bezier. This best result obtained by comparing with real figure and smoothness of the curve.